A Cross-Sectional Study of p66Shc Gene Expression in Liquid Biopsy of Diabetic Patients. Is it Possible to Predict the Onset of Renal Disease? - Diogo P. Simões; Matheus Moreira Perez; Beatriz da C. Aguiar Alves; Jéssica F. Araújo Encinas; Joyce R. Santos Raimundo; Catherine G. Costas Arcia; Vanessa Lopes Mathia; Maria I. Sacchi Mendonça; Laura B. Mesiano Maifrino; Neif Murad; Fernando L. Affonso Fonseca; Glaucia Luciano da Veiga (University Library System, University of Pittsburgh, 2023)
Background: Diabetic nephropathy (DN) is a disorder affecting glomerular function that, histologically, is due to the presence of glomerulosclerosis accompanied with endothelial dysfunction of the afferent and efferent renal arterioles. Insulin resistance in diabetic patients is known to be one of the causes of endothelial dysfunction because it increases oxidative stress, and one of the main genes regulating the production pathways of reactive oxygen species is p66Shc. The aim of this study was to evaluate the p66Shc gene expression as a precocious biomarker of renal dysfunction in diabetic patients, using liquids samples of urine sediment and peripheral blood. Methods: 29 diabetic patients and 37 healthy donors were recruited from the Centro Universitário FMABC outpatient clinic. The RT-gPCR technique was applied to evaluate p66Shc gene expression in urine and peripheral blood samples from diabetic patients, which were compared with healthy donors. Results: There was no significant expression of p66Shc gene in samples from diabetic patients compared with healthy donors. However, p66Shc expression in the blood samples of diabetics (0.02417±0.078652-ΔCT, n=29) was 3.6 times higher than in healthy participants (0.00689±0.01758, n=37) while in the urine samples, it was 1.48 times higher in diabetics group (0.02761±0.05412-ΔCT) than in CTL group (0.0186±0.02199). Conclusion: There was no significant p66Shc gene expression in peripheral blood and urine samples of diabetic patients without kidney injury compared with healthy donors, although there is a tendency for this gene to participate in the oxidative imbalance present in diabetes.